Strategi Pembuatan Konten Dakwah Di Media Sosial Dan Website Untuk Meningkatkan Engagement Umat - Muhammad Haeruddin (STAI Bumi Silampari, 2026)
This study aims to analyze strategies for creating da’wah content on social media and websites that can enhance community engagement. The research employs a qualitative approach with a descriptive research design, focusing on an in-depth understanding of digital da’wah phenomena in a contemporary context. The data sources consist of primary data in the form of da’wah content from various social media platforms and websites, as well as secondary data obtained from scholarly literature such as journal articles, books, and previous studies. Data collection techniques include literature review and content analysis, while data analysis is conducted using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing. The findings reveal five key strategies that are effective in increasing community engagement: audience segmentation, content differentiation and format innovation, interactivity, optimization of social media algorithms, and integration between social media and websites. These strategies are proven to enhance audience engagement both quantitatively and qualitatively through approaches that are relevant, adaptive, and user-oriented. Furthermore, cross-platform integration enables the establishment of a sustainable and structured digital da’wah ecosystem. The implications of this study highlight the importance of transforming da’wah strategies toward a more digital-oriented, data-driven, and communicative approach. This research is expected to serve as a reference for da’wah practitioners in designing more effective and innovative content capable of addressing the challenges of the digital era in enhancing community engagement sustainably.